Pengaruh Motivasi Intrinsik, Motivasi Ekstrinsik, Pemberdayaan Psikologis, dan Budaya Organisasi terhadap Organizational Citizenship Behavior - Wisnu Praja Mukti; Ignatius Soni Kurniawan; Jajuk Herawati (SEIKO : Journal of Management & Business, 2022)
Abstract Organizational Citizenship Behavior (OCB) is one of the contributing factors to the success of a company's performance. This research was conducted on employees of PT Baja Mulia Industrindo to explore the relationship between intrinsic motivation, extrinsic motivation, psychological empowerment, and organizational culture on OCB. This research is a quantitative research. This study used the census method with a total of 50 respondents. Data tested with Smart PLS version 3.0. This study found that intrinsic motivation has a non-significant negative effect on OCB, extrinsic motivation has a non-significant positive effect on OCB, psychological empowerment has a significant positive effect on OCB, and organizational culture has a significant negative effect on OCB. Keywords: Organizational culture; Extrinsic Motivation; Intrinsic Motivation; Organizational Citizenship Behavior; Psychological Empowerment.